Informed Consent: Is It Accompanied by Full Disclosure?. Issue 2 (March 2018) - Wilson, April; Rea, Brenda
Informed consent assumes full disclosure has been discussed in its entirety. However, is full disclosure ever really achieved? This column discusses how lifestyle medicine, both philosophically and ethically, must be a standard component of informed consent. Yet despite unequivocal evidence regarding the efficacy of lifestyle medicine, few physicians even consider lifestyle medicine as a viable option in the informed consent process. Reasons for the lack of lifestyle medicine considerations are postulated and a potential solution through education of trainees is suggested. How one medical school is addressing the need for lifestyle medicine education through several initiatives is discussed. Last, we expect that trainees educated in lifestyle medicine will push the momentum forward toward the "tipping point" where lifestyle medicine will be a viable option in the informed consent process—only then will full disclosure truly be achieved.